HUBUNGAN ANTARA DERAJAT OBSTRUKSI SERANGAN AKUT ASMA DENGAN KADAR IgE, IFN- DAN IL-4 TOTAL SERUM - Kusuma, HMS. Chandra; Kalim, Kusworini Handono; Riawan, Wibi; Muid, Masdar (Jurnal Kedokteran Brawijaya, 2004)
ABSTRACT Acute bronchial asthma is a common medical emergency the world over. There now exists compelling evidence of a role for Th2-Th1 paradigm in the pathogenesis of asthma in children. We hypothesized that childhood asthma is associated with the activation of  Th2-Th1 lymphocytes whose products regulate at least in part, the expression of IgE, IFN-γ and IL-4 and thereby disease severity. Our aims, therefore were to compare the level of total IgE, total IL-4 and total IFN-γ in serum from asthmatic and non asthmatic control children matched for age and sex, and to attempt to correlate the IgE, IL-4, and IFN-γ total level of serum in the asthmatics children with disease severity. Fifty one children with acute asthma exacerbation were compare with thirty one no asthmatics normal children matched for age and sex. The level of IgE, IL-4, and IFN-γ were measured using Elisa. Asthma severity was assessed by a symptom score and spirometri. The level of IgE and Il-4 in the serum of the asthma were elevated as compared to the non asthmatic normal controls, whereas the IFN-γ was decreased. There was a significant correlation between elevated levels of IgE and IL-4 with the acute asthma exacerbation severity, whereas the decreased level of IFN-γ was not. Conclusions. The increased levels of IgE , IL-4 and the ratio of  IL-4/IFN-γ play a crucial role in the acute asthma exacerbation severity.